Solution-gelation transition of hydroxylpropyl methyl cellulose (HPMC) - Choy, Gincent Jin Sheng. (2009)
Many researches have been conducted in the study of controlled drug release matrix tablets and capsules involving synthetic water soluble cellulose modifications. These substances are popular due to their ability to incorporate a large percentage of the drug and still yield a product which is compatible with conventional production techniques. Hydroxypropyl Methyl Cellulose (HPMC) is one such cellulose ethers which are used in a wide variety of applications.